Analisis Kepuasan Pengguna pada Aplikasi Spotify di Kota Palembang dengan Menggunakan Metode Usability - Tri Wulandari, Dinda; M. Rudi Sanjaya; Dedy Kurniawan; Endang Lestari Ruskan (The Indonesian Journal of Computer Science, 2025)
Usability level is one of the methods that can affect the comfort of mobile application users, and evaluation is very important to do. Spotify, as an app for listening to music and podcasts, has users from different parts of the world. The evaluation is carried out with the aim of improving the user experience, so that the application can evolve and be easier to use. The method applied in this evaluation is usability testing. The results obtained show that the Spotify application is of good quality, effective, efficient, and able to provide satisfaction to users, although there is still room for improvement to meet user expectations even better.